Usefulness of semiquantitative PCR‐Invader assay for selecting candidates for daclatasvir plus asunaprevir combination therapy among patients with hepatitis C virus genotype 1b. Issue 4 (27th November 2017) - Honda, Koichi; Seike, Masataka; Oribe, Junya; Endo, Mizuki; Arakawa, Mie; Tokoro, Masanori; Iwao, Masao; Mori, Tetsu; Nishimura, Junko; Takahashi, Yukou; Omori, Kaoru; Yamashita, Tsutomu; et al.
Abstract : Aims: PCR‐Invader is a highly sensitive assay for detecting non‐structural protein 5A (NS5A) resistance‐associated variants (RAVs) of hepatitis C virus (HCV). Here, we validated the accuracy of the semiquantitative PCR‐Invader (SQ‐PI) assay compared to direct sequencing (DS) for identifying NS5A RAVs, and we evaluated the treatment efficacy of daclatasvir plus asunaprevir (DCV + ASV) for patients judged to be non‐positive for NS5A RAVs by SQ‐PI. Methods: Detection rates of NS5A RAVs by SQ‐PI and DS were compared for 204 patients with HCV genotype 1b. Patients with non‐positive results for NS5A RAVs by SQ‐PI were treated by DCV + ASV, and the efficacy of this treatment was examined. Results: All samples judged as negative for NS5A RAVs by SQ‐PI were similarly judged by DS. However, 29.7% of samples judged as negative for Y93H by DS were judged as weakly positive or positive by SQ‐PI. Among 108 patients who were judged as negative by SQ‐PI and treated by DCV + ASV, rates of sustained virologic response at 24 weeks (SVR24) were 96.3% in intention‐to‐treat analysis and 99.0% in patients who completed treatment. Among patients who were weakly positive for Y93H on SQ‐PI, the SVR24 rate was 95.0% (19/20). This rate was 100% (78/78) in patients who were negative for Y93H on SQ‐PI and completed treatment. Conclusion: Treatment efficacy of DCV + ASV was extremely high among patients who were non‐positive for NS5A RAVs on SQ‐PI, especially for patients with negative results.